2017
DOI: 10.1111/and.12759
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-induced male infertility: Effects of aqueous leaf extract ofTetracarpidium conophorum

Abstract: This study investigated the effects of Tetracarpidium conophorum leaf extract on infertility induced by ethanol in male rats. Thirty rats were randomly divided into six groups of five animals each: Group 1 (positive control) received 0.9% saline only; Group 2 (ethanol alone) were given only 30% ethanol orally at 7 ml/kg body weight per day, thrice in a week; groups 3, 4 and 5 were given ethanol and co-treated with 50, 500 and 1,000 mg/kg body weight of leaf extract, respectively, while Group 6 was given ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 41 publications
1
31
0
1
Order By: Relevance
“…Arginase plays an important role in the metabolism/regulation of arginine (Akomolafe et al, ). As the activity of arginase increases under the diabetic state, arginine is depleted and there is reduction in the synthesis of NO below physiological levels (Chang, Liao, & Kuo, ; Nikolic, Cvetkovic, & Sokolovic, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arginase plays an important role in the metabolism/regulation of arginine (Akomolafe et al, ). As the activity of arginase increases under the diabetic state, arginine is depleted and there is reduction in the synthesis of NO below physiological levels (Chang, Liao, & Kuo, ; Nikolic, Cvetkovic, & Sokolovic, ).…”
Section: Discussionmentioning
confidence: 99%
“…The epididymis was surgically removed and weighed. The epididymis was placed in physiological saline (0.9%) in the ratio of 1:5 weight (g) by volume (mL) (Akomolafe, Oboh, Akindahunsi, & Afolayan, ), and gently punctured using a sterile pin to release the sperm cells. The medium containing sperm cells was used for the estimation of the sperm parameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased lipid peroxidation in the presence of Fe 2+ could be attributed to the fact that Fe 2+ can catalyze one-electron transfer reactions that generate ROS such as reactive hydroxyl radical ( • OH) which is formed from H 2 O 2 through the Fenton reaction. Iron also decomposes lipid peroxides, thus generating peroxyl and alkoxyl radicals, which favors the propagation of lipid peroxidation [33,34] The natural phenolic compounds and flavonoids have received increasing interest in the last years They may reduce the risk of development of several diseases caused by oxidative stress, including neurodegenerative disorders [35] and testes injury [36,37]. Their protective effects stem for the ability to inhibit lipid peroxidation, chelat redox-active metals (by binding iron), and attenuate other processes involving reactive oxygen species (such as through radical scavenging) [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Drinking will also affect male fertility, the regulating effects of neuroendocrine gonadal axis, through direct effects on testis spermatogenic and hormone produced in the environment affected by the effects on sperm quality led to a decline in the number of hormone levels decreased by [5] . Studies have shown that the incidence of [6] male infertility is associated with heavy drinking, and alcohol consumption may be one of the principal causes of male infertility.…”
Section: Effects Of Alcohol and Tobacco On Male Fertilitymentioning
confidence: 99%